2013
DOI: 10.1002/cncr.28045
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 study of cetuximab in combination with 5‐fluorouracil, cisplatin, and radiotherapy in patients with locally advanced anal canal carcinoma

Abstract: BACKGROUND: This study sought to determine the feasibility and recommended phase 2 dose (RP2D) of the combination of cetuximab with chemoradiotherapy based on 5-fluorouracil (5-FU) and cisplatin (CP) in locally advanced anal canal carcinoma. METHODS: Cetuximab was administered on days 1,8,15, 29, 36, 43, and 50 (400 mg/m 2 initial dose, then 250 mg/m 2 /week) concurrent with total dose radiation of 55 to 59 Gy, both starting on day 1. Escalating doses of 5-FU (96-hour infusion) and CP (2-hour infusion), both o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 26 publications
1
32
1
1
Order By: Relevance
“…To the author’s knowledge no positive data exist regarding the use of cetuximab in a curative setting. One phase I trial and one phase II trial of patients with locally advanced anal cancer receiving 5-FU, cisplatin, cetuximab and radiotherapy reported inhomogeneous efficacy and a extremely high number of serious adverse effects (SAEs) [24,25]. Further studies in large population are required to identify the prognostic role of cetuximab and the influence of HPV and other biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…To the author’s knowledge no positive data exist regarding the use of cetuximab in a curative setting. One phase I trial and one phase II trial of patients with locally advanced anal cancer receiving 5-FU, cisplatin, cetuximab and radiotherapy reported inhomogeneous efficacy and a extremely high number of serious adverse effects (SAEs) [24,25]. Further studies in large population are required to identify the prognostic role of cetuximab and the influence of HPV and other biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…High toxicity was observed also in other clinical trials2021, suggesting that the relation between toxicity, chemotherapy dosage and radiation techniques should be better clarified to optimize this promising combination treatment strategy for SCAC. In addition to this data, a recent case report has shown a dramatic response to cetuximab in combination with cisplatin and 5-FU in a patient with metastatic anal cancer9.…”
Section: Discussionmentioning
confidence: 85%
“…Deutsch et al reported a Phase II study of cetuximab combined with cisplatin/5FU CRT [22], while Olivatto et al reported a Phase I trial with a fixed dose of cetuximab and escalating doses of 5FU and cisplatin [23]. Significant toxicity led to early stopping of both trials suggesting that cetuximab cannot be integrated safely into CRT regimens.…”
Section: Strategies To Improve Crt Resultsmentioning
confidence: 99%